International Labor Market Competition and Spousal Labor Supply Responses - Pal Schone; Marte Strom (Institute of Labor Economics (IZA), 2019)
We study how the 2004 EU enlargement to Eastern European countries has affected employment, earnings and the sharing of home production among workers employed in the Building and Construction industry, and their wives. We use license requirements to divide workers into two groups who are more and less exposed to labor market competition. We find that non-licensed workers experience a fall in labor earnings relative to licensed workers after the EU enlargement. Increased wife's labor supply and earnings compensate almost 40 percent of the loss. We do not find a similar change in the division of labor in home production.
Keywords: J21; J22; J61; 330; immigration; female employment; division of labor; parental leave